Discourses of heritage : implications for archaeological community practice. - Laurajane Smith (Nuevo mundo - Mundos Nuevos, 2012)
This paper summarises previous arguments about the existence and nature of a Western and Eurocentric Authorised Heritage Discourse and examines the consequences this discourse has for archaeological practices associated with community engagement and outreach. This discourse frames archaeology heritage practices and works to conceive heritage as specifically ‘archaeological heritage’. The archaeological discipline owes much to the existence of this discourse, which privileges expert values over those of community and other sub-national interests and which works to constrain understandings of heritage as primarily material. This discourse hinders productive and critical community engagement and the paper argues that archaeologists need to engage in self-conscious and explicit challenges to this discourse to facilitate meaningful community partnerships.